Psycholinguistic properties of the Russian words and their visual correlates in the linguistic conscience of Tuvan-Russian bilinguals: an experiment-based study - Kolmogorova, Anastasia V. (The New Research of Tuva, 2021)
The article summarizes the outcomes of a study of psycholinguistic properties of the Russian words and their visual correlates in linguistic conscience of Tuvan-Russian bilinguals. By describing the different courses that cognitive processes take in monolinguals and bilinguals, the study provides some material for consideration by the theory of language contacts, as well as bi- and translingualism. The materials suggest that natural bilingualism is adaptive in its nature. The article shows that due to close contacts between the two cultures under Tuvan-Russian bilingualism, Russian words have a different set of systemic relations in bilingual’s mental lexicon, as compared to Russian monolinguals. One of the ways to trace this difference is through an experiment-based study. In our experiment, we used two sets of words and corresponding pictures: 1) list of common Russian nouns naming objects (e.g. “window”, “car” or “table”) and 2) nouns evoking phenomena and objects, which are of particular importance for the Tuvans (e.g. “horse”, “yurt”). As reference corpus, we took the results previously obtained by the research group of the Center of Language and Brain (High School of Economics) on the population of 100 neurologically healthy Russian monolinguals. Our population of informants consisted of 60 Tuvan-Russian bilinguals without any speech pathology (average age =21, 3). By the end of the experient, we obtained the values of such psycholinguistic properties as “age of acquisition”, “imageability” for 131 Russian words and “image agreement”, “image complexity” ‒ for their visual correlates. Using methods of linguistic experiment, comparative analysis showed that the variation between the values of all four properties for verbal and visual stimuli in the two groups of informants is statistically significant. However, while comparing the properties’ values of stimuli from the first set and from the second in bilinguals, we discovered that they master culturally-loaded nouns later than those of set 1, assess them as less imageable and perceive the illustrating pictures as more complex and less similar to their mental image. The evidence obtained evidences will help us in further work on developing speech exercises and albums for neuropsychological diagnostics and speech therapy of Tuvan-Russian bilinguals with aphasia.